(untitled) (Baghdad Science Journal, 2015)
A new series of morpholine derivative were prepared by reacting the morpholine with ethyl chloro acetate in the presence triethylamine as an catalyst and benzene as a solvent gave the ethyl morpholin-4-ylacetate reaction with hydrazine hydrate and ethanol as a solvent gave the 2-(morpholin-4-yl)acetohydrazide gave series of Schiff base were prepared by reacting 2-(morpholin-4- yl)acetohydrazide with different aromatic aldehydes and ketons . The new series of (3-9 )were synthesis by reaction of Schiff base (10-14) with chloroacetyl chloride, triethyl amine as an catalyst and 1,4dioxane as a solvent .The chemical structures of the synthesis compound were identified by spectral methods their [ IR ,1H-NMR and 13C-NMR ].The synthesised compounds were screened for antibacterial activity and antifungal activity promising by disc diffusion method by measuring the zone of inhibition and the results were compared to standard drugs ciprofloxacin .